Profitabilitas Sub Sektor Transportasi Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Solikahan, Eka Zahra; Ariawan , Ariawan; Olii, Nurhayati (Al-Buhuts, 2023)
Profitability is one of the indicators that show the financial performance of a company. The higher the profitability of the company reflects the better the company is in generating profits. However, in practice there are many factors that must be considered to increase profitability. Therefore, the purpose of this study is to analyse the factors that affect profitability such as leverage, working capital, liquidity and company growth. The population in this study are transportation sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique is Purposive Sampling with a total sample of 30 companies during the 2017-2021 period. The data analysis technique uses panel data regression analysis using Eviews software. The results of this study indicate that leverage and working capital have an effect and are not significant to profitability. Liquidity and company growth have no effect on profitability on profitability